Instilling Nationalism and Love for the Homeland in Young Indonesian Immigrants in the Sentul Region of Malaysia - Muthia Fadhilah Husni; Rachma Chairunnisa Utani; Yolanda Sasmita Putri; Indah Ainun Mutiara; Suyanto Suyanto; Santosa Pradana Putra Setya Negara; Erwin Prasetyo (International Conference on Education for All, 2023)
This article discusses the importance of instilling nationalism and love for the homeland in young Indonesian immigrants, particularly in the Sentul region of Malaysia, who face challenges in accessing education in the host country due to a lack of essential documents. Education is identified as the primary foundation for shaping children's characters, and as such, this research highlights the urgency of addressing this issue. The purpose of this community service is to provide understanding and instill nationalism and love for the homeland in young Indonesian immigrants in the Sentul region of Malaysia. The results of this community service demonstrate a significant improvement in instilling the values of nationalism through character education, particularly the values of Pancasila, which can be implemented in their education.